2017
DOI: 10.1186/s13028-016-0274-8
|View full text |Cite
|
Sign up to set email alerts
|

Catestatin and vasostatin concentrations in healthy dogs

Abstract: BackgroundThe neuroendocrine glycoprotein chromogranin A is a useful biomarker in humans for neuroendocrine tumors and stress. Chromogranin A can be measured in both blood and saliva. The objective of this study was to investigate concentrations of and correlation between the chromogranin A epitopes catestatin and vasostatin in healthy dogs accustomed to the sample collection procedures. Blood and saliva samples were collected from 10 research Beagle dogs twice daily for 5 consecutive days, and from 33 private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 79 publications
2
40
1
Order By: Relevance
“…Furthermore, layer flocks, which spend longer time in the poultry house, had higher prevalence of Salmonella infection compared with broiler flocks. Wierup et al [49] have also showed a substantially higher prevalence of Salmonella in layer flocks than in broilers among outdoor and indoor housing system. A high number of Salmonella serotypes were observed in the farms investigated suggesting either a wide diversity of sources for introduction of Salmonella into the farms, or that common sources (such as contaminated feed) can contain different serotypes over time.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, layer flocks, which spend longer time in the poultry house, had higher prevalence of Salmonella infection compared with broiler flocks. Wierup et al [49] have also showed a substantially higher prevalence of Salmonella in layer flocks than in broilers among outdoor and indoor housing system. A high number of Salmonella serotypes were observed in the farms investigated suggesting either a wide diversity of sources for introduction of Salmonella into the farms, or that common sources (such as contaminated feed) can contain different serotypes over time.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, layer flocks, which spend longer time in the poultry house, had higher prevalence of Salmonella infection compared with broiler flocks. Wierup et al [ 49 ] have also showed a substantially higher prevalence of Salmonella in layer flocks than in broilers among outdoor and indoor housing system.…”
Section: Discussionmentioning
confidence: 99%
“…Post-weaning diarrhea (PWD) is of critical concern in swine production worldwide and can typically result in lower feed intake, growth retardation, and immune suppression [ 1 ]. A previous report has established that Escherichia coli is the predominant pathogenic strain causing PWD in piglets [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously showed that composite pain scales are more reliable than simple one-dimensional pain scales like the Visual Analogue Scale (VAS) (8). The VAS is a subjective tool (9) and the rater is asked to make an estimate of the pain of the patient placing a mark on a 10 cm-line. The VAS is an effective tool in human medicine (10), when a selfassessment is performed, whereas its use in veterinary medicine comes with limitations, since the assessment is performed on another individual belonging to another species.…”
Section: Introductionmentioning
confidence: 99%